Equilibrium of knowledge vs. money functions explaining intentions to sustainable food consumption - Behjati, Saeed; Kumar M., Dileep (Centre of Promoting Research Excellence, 2012)
Develop strategies to change customer behavior on food consumption, requires an understanding of consumer behavior and other influential factors.Therefore, in this study with advantage of the theory of planned behavior (Ajzen, 1988) investigate some on consuming purchasing and consuming intention. This study gives insight into consumer behavior, factors affecting the sustainable consumption, hurdles of purchasing pro environmentally options; purchase environmentally friendly products Consciously, and also marketing insight into sustainable environmental friendly via measurement and evaluation intention of purchase.The results deeply reveal that Price consciousness parallel with pro-environmental concerns influences the intention to move towards sustainable food consumption.